The Implementation of Special Autonomy in The Papua Province in Public Health Policies in Order to Strengthen The Unified Republic of Indonesia - Sebedeus Hitokdana; I Gusti Ayu Ketut Rahmi Handayani; Djoko Wahju Winarno; Sofyan Wimbo Agung Pradnyawan (Health Notions, 2018)
The Province of Papua is a province in Irian Jaya which is later changed to Papua Province. It is granted a special autonomy within the framework of the Unified Republic of Indonesia. The special autonomy is a special authority recognized and granted by the central Indonesian government to the provincial government of Papua to regulate and manage the interest of local people according to their own initiatives based on the aspiration of the Papua people. The method of this research was a descriptive empirical law. The sources of data research used were both primary and secondary data. Based on the result of the study, it could be concluded that the implementation of the special autonomy law in Papua is basically a special authority recognized and given for the province of Papua to regulate and manage their own household affairs. The special autonomy of Papua is a rule or a policy given by the Indonesian central government to the Papua province in order to increase the efforts in various aspects, namely education, health, and infrastructure using a special autonomy. Keywords: Implementation, Special autonomy, Unitary state